Three‐dimensional printing for surgical planning of a double aortic arch case. Issue 4 (24th February 2020) - Arcieri, Luigi; Provost, Bastien; Charbonneau, Philippe; Fournier, Emmanuelle; Hascoet, Sebastien; Le Bret, Emanuel
Abstract: Background and Aim: Over the past years, three‐dimensional (3D) models of patient‐specific anatomical conditions are being used to improve the comprehension and surgical management of a variety of diseases. It is an additional diagnostic tool that aids clinical decision‐making. Furthermore, this technology is still not routinely used in the medical field since its availability is limited by cost and complex process. Methods and Results: We describe a patient with a balanced‐type double aortic arch encircling trachea and esophagus. Considering the clinical symptoms, surgical decompression of these structures and defined aortic arch reconstruction was indicated. The 3D printed model revealed narrowing of the left aortic arch at the junction of the descending thoracic aorta that did not clearly appear on the conventional images reconstruction. The left aortic arch was divided and the symptoms completely disappeared. No immediate or late complications occurred. Conclusion: 3D printed models can be helpful in surgical planning of congenital heart malformations. It should be strongly considered as an additional tool in complex cases.